Pengaruh Kompetensi Kewirausahaan Terhadap Perkembangan Usaha Mikro, Kecil, Dan Menengah (UMKM) Perempuan Di Kota Bandung - Tantina, Benita Lexie (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Entrepreneurial competence plays an important role in the success of micro, small, and medium enterprises (MSMEs). This study aims to analyze the influence of entrepreneurial competence on the development of women-owned MSMEs in Bandung City. Using a descriptive quantitative method with a purposive sampling approach, this study involved 40 respondents who were women MSME owners in Bandung. The results show that entrepreneurial competence has a significant positive effect on the development of MSMEs, especially in the aspects of organizing and strategic commitment. This study provides important implications for the development of MSMEs through more targeted entrepreneurship training and policy support.